1999
DOI: 10.1364/ao.38.005350
|View full text |Cite
|
Sign up to set email alerts
|

Aberration-free dynamic focusing with a multichannel micromachined membrane deformable mirror

Abstract: We demonstrate aberration-free dynamic focusing with a low-cost 19-channel continuous-surface micromachined membrane deformable mirror (MMDM). A lookup table of the optimum control voltages for various focal lengths is obtained with an adaptive optics algorithm. Diffraction-limited imaging resolution is achieved owing to the capability of the MMDM for aberration compensation. The measured speed of the MMDM supports dynamic focusing operations at several hundred hertz. Our dynamic focusing approach is shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In such techniques, scanning different axial planes requires the objective lens to be physically moved with an actuator, such as a stepper motor or a nanopositioner, a process which is temporally limited by the combined inertia of objective lens and actuator. Several methods have been developed to quickly change the focal position, and thus allow for axial scanning, including deformable mirrors 25 , variable focus liquid-filled lenses 26 , and simultaneous spatial and temporal focusing 27,28 . However, none have the ability to simultaneously scan in the lateral dimension, and none have been demonstrated to functionally image parameters of neuronal activity.…”
Section: Introductionmentioning
confidence: 99%
“…In such techniques, scanning different axial planes requires the objective lens to be physically moved with an actuator, such as a stepper motor or a nanopositioner, a process which is temporally limited by the combined inertia of objective lens and actuator. Several methods have been developed to quickly change the focal position, and thus allow for axial scanning, including deformable mirrors 25 , variable focus liquid-filled lenses 26 , and simultaneous spatial and temporal focusing 27,28 . However, none have the ability to simultaneously scan in the lateral dimension, and none have been demonstrated to functionally image parameters of neuronal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods for fast focusing, such as deformable mirrors (Zhu et al 1999), fluid-filled lenses (Zhang et al 2003), and electro-optic lenses (Shibaguchi and Funato 1992), have all been shown and are possibilities for offering fast 3D scanning when combined with either galvanometers or other 2D scanning methods. However, to our knowledge, none has yet been shown in two-photon imaging systems.…”
Section: D Scanning Systemsmentioning
confidence: 99%
“…Compared to the liquid lenses optical zoom system, the deformable mirror zoom system has a distinct advantage of being free of chromatic aberrations. [23][24][25] So we employ two deformable mirrors to be variable elements to realize an optical zoom in our system. The principle part of the system consists of a Cassegrain and a Cassegrain-inverse configuration.…”
Section: Active Optical System For Anymentioning
confidence: 99%